2021
DOI: 10.5194/esurf-2020-108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise water level measurements using low-cost GNSS antenna arrays

Abstract: Abstract. We have developed a ground-based Global Navigation Satellite System Reflectometry (GNSS-R) technique for monitoring water levels with a comparable precision to standard tide gauges (e.g., pressure transducers) but at a fraction of the cost and using commercial products that are straightforward to assemble. As opposed to using geodetic-standard antennas that have been used in previous GNSS-R literature, we use multiple co-located low-cost antennas to retrieve water levels via inverse modelling of Sign… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…The data collected at Trois-Rivières and Saint-Joseph-de-la-Rive has been uploaded to the repository D. Purnell et al (2023). The software is available at https://github.com/purnelldj/gnssir_rt and has been permanently archived at (D. Purnell, 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The data collected at Trois-Rivières and Saint-Joseph-de-la-Rive has been uploaded to the repository D. Purnell et al (2023). The software is available at https://github.com/purnelldj/gnssir_rt and has been permanently archived at (D. Purnell, 2023).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Such installations have far superior reflection characteristics at the cost of poor positioning capabilities. GNSS‐IR also benefits from using an inexpensive GNSS antenna which does not mitigate reflections to the same extent as larger geodetic antenna (Fagundes et al., 2021; Purnell et al., 2021; Williams et al., 2020).…”
Section: Gnss Interferometric Reflectometry For Water Level Measurementsmentioning
confidence: 99%
“…Purnell et al. (2021) employed a stack of side‐facing low‐cost antenna and receivers (total cost ∼ $200–300 U.S. dollars including solar panel and battery) to track the L1 frequency of multiple GNSS constellations. The water surface reflections extended more than 140° in azimuth and over a range of elevation angles up to 50°.…”
Section: Gnss Interferometric Reflectometry For Water Level Measurementsmentioning
confidence: 99%
“…This technique is named as GNSS-Interference/Maltipath Reflectometry (GNSS-I/MR), which could provide centimeterlevel altimetry precision. Geodetic antenna and receiver are designed to reduce multipath signals so that only GNSS signals from the low elevation angle satellites are used to measure sea surface height, therefore this approach based on geodetic antenna and receiver has low temporal resolution [28]. A 10year comparison of water levels measured using a geodetic GPS receiver versus tide gauge was carried out, and the results showed that the daily sampling number of individual estimations from GPS is from 20 to 40, and the corresponding sampling rate is from 0.6 to 1.2 h [29].…”
Section: Introductionmentioning
confidence: 99%
“…A 10year comparison of water levels measured using a geodetic GPS receiver versus tide gauge was carried out, and the results showed that the daily sampling number of individual estimations from GPS is from 20 to 40, and the corresponding sampling rate is from 0.6 to 1.2 h [29]. To use the signals over a greater range of satellite elevation angles, multiple lowcost antennas were used to measure water level in [28]. The results found that using a larger range of elevation angle can eliminate the gaps in time for daily tidal variation, however, the measurements were generally less precise at elevation angles greater than 30 • because of lower RHCP components in signals.…”
Section: Introductionmentioning
confidence: 99%